EXPLORING THE UTILIZATION OF THE TASK-BASED APPROACH ON UNIVERSITY STUDENTS SPEAKING ABILITY IN THE ENGLISH LANGUAGE - Ahmed, Babikir Eltigani Siddig (IJRDO- Journal of Educational Research, 2017)
This paper examines the implications of the application of Task-Based Method amongst university students’ English language proficiency. The current learning environment is impacted with teaching and exposing students to the second language given its prevailing benefits. Nevertheless, the problem of the appropriate approach that teachers and students should to foster effective teaching and learning respectively. This study employed a mixed method approach with both quantitative and qualitative analysis utilized to answer the formulated research objectives. 100 research subjects were recruited from the University of Khartoum through convenient sampling. Data collected from the study was analyzed both qualitatively and quantitatively through the SPSS 21.0 and thematic analysis respectively. Results from the t-test and Spearman’s correlation indicated the existing relationship between utilization of Task-Based Method and the university students’ English speaking ability.